The role of auditory temporal cues in the fluency of stuttering adults - Furini,Juliana (2017)
ABSTRACT Purpose: to compare the frequency of disfluencies and speech rate in spontaneous speech and reading in adults with and without stuttering in non-altered and delayed auditory feedback (NAF, DAF). Methods: participants were 30 adults: 15 with Stuttering (Research Group - RG), and 15 without stuttering (Control Group - CG). The procedures were: audiological assessment and speech fluency evaluation in two listening conditions, normal and delayed auditory feedback (100 milliseconds delayed by Fono Tools software). Results: the DAF caused a significant improvement in the fluency of spontaneous speech in RG when compared to speech under NAF. The effect of DAF was different in CG, because it increased the common disfluencies and the total of disfluencies in spontaneous speech and reading, besides showing an increase in the frequency of stuttering-like disfluencies in reading. The intergroup analysis showed significant differences in the two speech tasks for the two listening conditions in the frequency of stuttering-like disfluencies and in the total of disfluencies, and in the flows of syllable and word-per-minute in the NAF. Conclusion: the results demonstrated that delayed auditory feedback promoted fluency in spontaneous speech of adults who stutter, without interfering in the speech rate. In non-stuttering adults an increase occurred in the number of common disfluencies and total of disfluencies as well as reduction of speech rate in spontaneous speech and reading.